Logitech / Muhammad Nasrul Ahmad - Ahmad, Muhammad Nasrul (2022)
A Swiss company focused on innovation and quality, Logitech designs products and experiences that have an everyday place in people's lives. Founded in 1981 in Lausanne, Switzerland, and quickly expanding to the Silicon Valley, Logitech started connecting people through innovative computer peripherals and many industry firsts, including the infrared cordless mouse, the thumb-operated trackball, the laser mouse, and more. Logitech’s product strategy is focused on the screens that people use as their window into their digital world. We study how people use theirs screens ( laptop PC or Mac, tablets, TV, Smartphone and meeting room screens ) and create products that enhance their experience with those screens, whether they are using them as consumer or as participants in a business This is a great opportunity to learn and collect general information about the company and their product. By researching the background of the company, technology they been use and the innovation they came up on producing their product. This might be a stepping stone for me literally speaking on making my own product. By deducing the SWOT analysis that have been distinguish from strength, weakness, opportunities and threats of the company I can make or innovate out a better technology based on the data that have been collected and not just that, with this particular method I can cope the current issue by planning and improve the existing system in business development growth.